2012
DOI: 10.1021/ef201473j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diluent Addition on Bitumen Liberation from a Glass Surface

Abstract: Liberation of bitumen from sand grains is a key step on processing oil sands using water-based extraction processes. In this study, effects of diluent addition on bitumen liberation from a solid surface were investigated under various conditions, including the washing temperature, pH value of the water, and washing time. It was found that more effective bitumen liberation could be achieved by adding diluents, such as kerosene and fatty acid methyl ester (FAME), in the bitumen. Especially, FAME addition was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…It was also reported in our previous study that the bitumen liberation from a glass surface was greatly improved as the bitumen viscosity decreased by addition of diluents in the bitumen. 28 In this study, the great decrease of the bitumen viscosity enhanced the flowability of bitumen and then facilitated the bitumen liberation and recovery. The SARA fraction analysis showed that the decrease of the bitumen viscosity was attributed to the microbial degradation of the asphaltenes.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…It was also reported in our previous study that the bitumen liberation from a glass surface was greatly improved as the bitumen viscosity decreased by addition of diluents in the bitumen. 28 In this study, the great decrease of the bitumen viscosity enhanced the flowability of bitumen and then facilitated the bitumen liberation and recovery. The SARA fraction analysis showed that the decrease of the bitumen viscosity was attributed to the microbial degradation of the asphaltenes.…”
Section: Discussionmentioning
confidence: 65%
“…A similar phenomenon has been reported in the previous study, which was attributed to the reduce of the gel-type microstructure or the break-up of the continuous network of the asphaltene particles in bitumen at higher shear rate. 28 It was worthy to note that the viscosity of the microbial-treated bitumen decreased one order of magnitude comparing with that of the original bitumen. It is believed that the asphaltene molecules in bitumen are easy to be aggregated and surrounded with the resins.…”
Section: Rheological Characterization Of Bitumenmentioning
confidence: 98%
See 3 more Smart Citations